O uso de laserterapia como método complementar no tratamento de ferida cutânea em gata: um relato de caso - FARIAS, Daiara Joana Lima de (2024)
The use of Low-Level Laser Therapy (LLLT) is described as an alternative method in the treatment of cutaneous wounds. As a complementary and innovative therapeutic resource, it is possible to use low intensity beams as an ancillary therapy in the treatment of cutaneous wounds. The present report aims to present a case of a female feline patient, spayed, mixed breed, of approximately 1 year old, with a history of apathy and inappetence. The patient was admitted on March 29, 2023, on a private veterinary clinic located in Castanhal, Pará. She presented a cutaneous lesion measuring approximately 10 cm over the lumbosacral region, for which LLLT was used as an alternative treatment. At the first appointment, after shaving, ulcerations were observed in the wound, and manual debridement was performed. For better monitoring of the wound’s evolution, the patient was hospitalized. Initially, treatment was carried out with a hydrocolloid dressing, which provided autolytic debridement within 48 hours. After this period, the dressing was removed, and treatment continued with the use of Kollagenase ointment once a day for 14 days. Subsequently, the treatment was changed to the combination of 1% silver sulfadiazine ointment once a day with LLLT sessions every 48 hours, totaling 9 sessions. At the end of this treatment period, there was a significant improvement in the lesion, with a reduction in wound size of approximately 90%. The patient was discharged at the end of the laser sessions, with recommendations for daily dressings at home until complete wound healing.